1989
DOI: 10.1111/j.1545-5300.1989.00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Putting the Illness in Its Place: Discussion Groups for Families with Chronic Medical Illnesses

Abstract: A new psychosocial intervention for families and patients experiencing the chronic phase of a disabling medical illness is described. The intervention, a short-term, highly structured, psychoeducationally oriented, multiple-family discussion group (MFDG), was developed within the context of a clinical research program and has been successfully applied to a heterogeneous range of disabling medical illnesses. This report includes a detailed description of the treatment model, the format and content of group meet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
117
0
4

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(123 citation statements)
references
References 31 publications
2
117
0
4
Order By: Relevance
“…Strategies to intervene with natural networks include education among the women with lymphedema and their network members to improve communication, social, and relationship skills, remove structural barriers to interacting, and build stronger social ties [12,48]. Examples from previous behavioral research has shown that family support groups, visitation programs, and the development of new social networks for family members can strengthen natural helper networks [48][49][50][51][52][53][54][55][56]. For the most disabled women, socially isolated, and without natural social networks, interventions replacing impoverished or extinguished networks may be necessary.…”
Section: Practice Implicationsmentioning
confidence: 99%
“…Strategies to intervene with natural networks include education among the women with lymphedema and their network members to improve communication, social, and relationship skills, remove structural barriers to interacting, and build stronger social ties [12,48]. Examples from previous behavioral research has shown that family support groups, visitation programs, and the development of new social networks for family members can strengthen natural helper networks [48][49][50][51][52][53][54][55][56]. For the most disabled women, socially isolated, and without natural social networks, interventions replacing impoverished or extinguished networks may be necessary.…”
Section: Practice Implicationsmentioning
confidence: 99%
“…Multiple-family group intervention has been used as a generic intervention for a variety of problems, including chronic mental illness~Gonzalez, Steinglass, & Reiss, 1989, McFarlane, 2002McFarlane, Link, Dushay, Marchal, &Crilly, 1995! anddually diagnosed adolescents~Kymissis, Bevacqua, &Morales, 1995!. In interventions with various populations, the focus is on increasing positive parenting practices, improving family communication, and creating a community of shared experiences.…”
Section: An Alternative Approach: Multiple-family Group Interventionmentioning
confidence: 99%
“…Multi-family groups sup-ported by the culture of a psychiatric unit would provide a supportive context in which family members could share these reactions, especially important since they often include powerful emotional experiences. 11 The presence of other adolescents with physical illness in a culture which supports verbalization of emotional reactions should further induce families to verbalize their experiences: While support for this can be given by some members of a treatment team on medical units, it is likely that the family will experience other treatment team members who exemplify denial of emotional reactions to illness. These reactions would be more accessible to therapeutic intervention in a setting where psychiatric treatment is the rule, rather than the exception.…”
Section: Rationalementioning
confidence: 98%